Integrating transcriptomics and metabolomics to analyze the defense response of Morus notabilis to mulberry ring rot disease - Qian, Qianqian; Deng, Xinqi; Mureed, Sumbul; Gan, Yujie; Xu, Danping; Wang, Xie; Ali, Habib (Frontiers in Microbiology, 2024)
The mulberry industry has thrived in China for millennia, offering significant ecological and economic benefits. However, the prevalence of mulberry ring rot disease poses a serious threat to the quality and yield of mulberry leaves. In this study, we employed a combination of transcriptomic and metabolomic analyses to elucidate the changes occurring at the transcriptional and metabolic levels in Morus notabilis in response to this disease infestation. Key metabolites identified were further validated through in vitro inhibition experiments. The findings revealed significant enrichment in KEGG pathways, particularly those related to flavonoid biosynthesis. Notably, naringenin, kaempferol, and quercetin emerged as pivotal players in M. notabilis's defense mechanism against this disease pathogen. The upregulation of synthase genes, including chalcone synthase (CHS), flavanone-3-hydroxylase (F3H), and flavonol synthase (FLS), suggested their crucial roles as structural genes in this process. In vitro inhibition experiments demonstrated that kaempferol and quercetin exhibited broad inhibitory properties, while salicylic acid and methyl jasmonate demonstrated efficient inhibitory effects. This study underscores the significance of the flavonoid biosynthesis pathway in M. notabilis's defense response against mulberry ring rot disease, offering a theoretical foundation for disease control measures.